The Crisis of Indian Secularism - Beltramini, Enrico (Exchange, 2021)
In this paper I suggest that Roman Catholic theologians in India take a second look at the distinction between western and Indian secularisms. Blurring the lines between western and Indian secularisms may help the theological reflection on the so-called crisis of Indian secularism. The key point is the non-ontological, historical character of secularism. A look at the growing literature on western post-secularization, in fact, may offer some suggestions about how to deal with the nationalist mooring of Hindutva philosophy. A possibility exists that both the West and India are eventually entering simultaneously, but not necessarily on the same terms, a post-secular phase.